USING OF ACTIVATED CARBON DERIVED FROM AGRICULTURE WASTE COATING BY LAYERED DOUBLE HYDROXIDE FOR COPPER ADSORPTION - & Abdul-Hameed, Al Juboury (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Mg/Fe layered double hydroxides (LDH) as highly effective clay adsorbents coating activated carbon derived from agricultural waste (AW) were prepared by activation of date palm leaf base (LB) synthesized on Mg/Fe layered double hydroxides. FTIR, SEM and EDS were used to characterize the obtained adsorbent for the copper removal from aqueous solutions. The evaluation of adsorption performances was carried out at various metal concentrations, adsorbent dosage, contact time, and pH. The pseudo-second-order kinetic and the Langmuir isotherm model showed a good compliance with the experimental data, the result demonstrated that the improving adsorption capacity and fast rating adsorption for Cu2+ resulted from successful intercalation of date palm petiole activated carbon into LDH.